Silent primary ovarian ectopic pregnancy following ovulation induction: diagnostic dilemma - Saidhandapani, Kalyani; Pandey, Yashaswi; Shaunthini, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Early diagnosis of an ovarian pregnancy, of all the diagnoses relating to extrauterine gestations, is perhaps a diagnostic challenge faced by an obstetrician and a radiologist. About 0.5% of extrauterine implantations occur in the ovary. Recent studies have demonstrated infertility and Assisted reproductive techniques (ARTs), multiparity, use of intrauterine devices as risk factors for ovarian ectopic. Knowledge pertaining to ovulation induction and risk of ovarian ectopic is even more scant. In this article, we report a case report of ovarian pregnancy following ovulation induction with letrozole. Patient visited with history of missed menstrual period, mild abdominal pain and a weakly positive urine pregnancy test. Provisional diagnosis of right tubal ectopic was made. Diagnosis of ruptured ovarian ectopic was made on explorative laparoscopy which was later confirmed histopathologically. Patient had normal intra and post-operative course. An ovarian ectopic can present as a life-threatening condition and a high index of suspicion can prevent morbidity as well as mortality. Ovarian pregnancy in a primigravida with ovulation induction without an alarming sign, as in this case, is the rarest entity came across till date.